2021
DOI: 10.3390/nu13103583
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes-Related Health Economic Impact Associated with Increased Whole Grains Consumption among Adults in Finland

Abstract: The prevalence of type 2 diabetes (T2D) is increasing rapidly worldwide. A healthy diet supporting the control of energy intake and body weight has major importance in the prevention of T2D. For example, a high intake of whole grain foods (WGF) has been shown to be inversely associated with risk for T2D. The objective of the study was to estimate the expected health economic impacts of increased WGF consumption to decrease the incidence of T2D in the Finnish adult population. A health economic model utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…While the expert roundtable acknowledged the higher cost of whole grain foods, they also noted this must be balanced by the potential public health benefit and cost savings in health care and quality of life that could be realized through increased whole grain intake. Several modeling studies in the United States, Europe, and Australia have consistently reported health care costs savings if individuals met the recommended intakes for whole grain (Abdullah et al, 2021; Martikainen et al, 2021; Murphy & Schmier, 2020). In the United States, if the population consumed the recommended amount of whole grain each day, the direct medical cost savings for cardiovascular disease alone was estimated to be $21.9 billion (Murphy & Schmier, 2020).…”
Section: Roundtable Discussion On Opportunities and Challenges In Ach...mentioning
confidence: 99%
“…While the expert roundtable acknowledged the higher cost of whole grain foods, they also noted this must be balanced by the potential public health benefit and cost savings in health care and quality of life that could be realized through increased whole grain intake. Several modeling studies in the United States, Europe, and Australia have consistently reported health care costs savings if individuals met the recommended intakes for whole grain (Abdullah et al, 2021; Martikainen et al, 2021; Murphy & Schmier, 2020). In the United States, if the population consumed the recommended amount of whole grain each day, the direct medical cost savings for cardiovascular disease alone was estimated to be $21.9 billion (Murphy & Schmier, 2020).…”
Section: Roundtable Discussion On Opportunities and Challenges In Ach...mentioning
confidence: 99%
“…In the present study, the societal perspective (excluding direct non-medical costs, such as travel costs associated with the utilization of health care services) was applied in the study. The excess primary health care cost estimates of T2D were obtained from a recent Finnish study ( Martikainen et al, 2021 ). The excess secondary health care costs of T2D, its complications and T2D-related productivity losses for persons under the age of 65 were based on previous Finnish studies ( Koski et al, 2017 ; Koski et al, 2018a ; Koski et al, 2018b ).…”
Section: Methodsmentioning
confidence: 99%
“…To model the risk of T2D-related micro- and macrovascular complications in persons with newly diagnosed T2D, a previously developed Weibull survival regression model was applied ( Martikainen et al, 2021 ). The coefficients of the Weibull regression for the incidence of T2D-related complications is shown in Supplementary Material S4 .…”
Section: Methodsmentioning
confidence: 99%
“…Several surrogate estimates have been applied worldwide to approximate whole grain intake instead of calculating total whole grain intake from the whole diet as recommended [6]. The estimates have mainly been based on the consumption of certain whole grain-containing foods, such as whole grain bread or breakfast cereals [7][8][9][10][11]. However, the accuracy of these estimates in relation to total whole grain intake has not been assessed.…”
Section: Introductionmentioning
confidence: 99%